Rancang Bangun Website Tour & Travel “Tourly” - Ramadhan, Adiva Riski; Nst, Anggi Zulfikarsyah; Asmara, Mhd. Reyhanz Fahreza; Zega, Hari Apriaman; Zebua, Grace Selvi Monica (Himpunan Dosen Gemilang Indonesia (HDGI), 2023)
This research aims to develop a website designed using a programming language aimed at tourists. Information is one of society's needs today. People in general want to get the information they want through various media, one of which is through websites. In general, people use websites as an option to access information more quickly, effectively and up to date. This website is designed to make it easier for tourists to order/buy tickets to visit their destination. Providing efficient solutions for tourists, as well as increasing the openness and accessibility of information for tourists. Involving iterative development methods and stakeholder participation, this website is expected to facilitate the flight or travel process for tourists. The success rate of this website in promotion via social media is still relatively low and requires evaluation because the number of likes, comments and shares is still small. However, on the other hand, consumers prefer to call the Tourly and Travel office number directly to ask about international tour packages rather than engaging in social media, so that the process of selling international tour packages continues.